Zero-Base Budgeting: Prospects for Developing a Semi-Confusing Budgeting Information System - Williams, John Joseph (Institutional Knowledge at Singapore Management University, 1981)
This paper argues for the recognition that zero-base budgeting (ZBB) is a destabilizing which may co-exist in the future with traditional budgeting systems (TBS) to form a semi-confusing information system. The stabilizing and destabilizing features of a semi-confusing information system are explored first. The characteristics of ZBB as a formal budgeting process are examined next to provide a comparative profile of its destabilizing features in a changing environment. Analytically, ZBB characteristics match with the destabilizing properties of a semi-confusing information system and this insight has substantial implications for the future use of ZBB.